2014
DOI: 10.1111/j.1532-950x.2014.12251.x
|View full text |Cite
|
Sign up to set email alerts
|

Incisional Colopexy for Treatment of Chronic, Recurrent Colocloacal Prolapse in a Sulphur‐Crested Cockatoo (Cacatua galerita)

Abstract: Incisional colopexy is feasible despite a bird's relative small body size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Barium contrast radiography has been used after surgery to correct recurrent colocloacal prolapse in a cockatoo (Cacatua galerita). 18 Contrast studies enable monitoring of the effectiveness of the colopexy in maintaining cloacal position and allowing normal gastrointestinal tract function. Where there is a risk of possible leakage, water-soluble contrast, such as iohexol, should be used in preference to barium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barium contrast radiography has been used after surgery to correct recurrent colocloacal prolapse in a cockatoo (Cacatua galerita). 18 Contrast studies enable monitoring of the effectiveness of the colopexy in maintaining cloacal position and allowing normal gastrointestinal tract function. Where there is a risk of possible leakage, water-soluble contrast, such as iohexol, should be used in preference to barium.…”
Section: Discussionmentioning
confidence: 99%
“…Individual studies have reported success in passerine and psittacine birds; however, no controlled study has, to our knowledge, been published. 17,18 Several options are available for monitoring patients after surgery. Barium contrast radiography has been used after surgery to correct recurrent colocloacal prolapse in a cockatoo (Cacatua galerita).…”
Section: Discussionmentioning
confidence: 99%